Optimasi Pencampuran Minyak Nabati Bebas Lemak Trans untuk Cokelat Isian Menggunakan Software Design Expert 13 - Panuju, Sherly; Sugiyono, Sugiyono; Hunaefi, Dase (Jurnal Teknologi dan Industri Pangan, 2024)
Restriction of trans fatty acids (TFA) in the diets due to their negative impacts on health has led to the development of various TFA-free products. Blending is one of the common methods used to obtain TFA-free fats. This study aimed to obtain optimum formula of TFA-free oil, designed by using Design Expert 13 mixture with a simplex-lattice design for chocolate filling application. There were four types of oils, namely palm oil (PO), palm olein (PL), palm kernel oil (PKO), and chemically interesterified palm oil (CIE). Analysis was performed on chemical and physical properties of the oil blends as well as the physical properties of chocolate filling made from the oil blends. Commercial partially hydrogenated oil (PHO) was used as a comparison. The results showed that two out of six oil blends were recommended by the software, and both conformed to the specifications of commercial PHO, namely E (blend of 48% CIE and 52% PL) and F (blend of 33% CIE, 21% PKO, 17% PL, and 29% PO). The induction period (IP) and crystallization rate of sample E and F are lower than PHO. All chocolate fillings showed good emulsion stability (oil released <0.1%). The texture of chocolate fillings F and E were softer than PHO. Principal component analysis and orthogonal partial least square-discriminant analysis graphs showed that all samples were located in different cluster, but sample F was closer to PHO compared to E. In conclusion, although the optimum blends obtained through the use of Design Expert had similar solid fat content to PHO, the chemical and physical characteristics of the oil blend and chocolate filling were significantly different from PHO. Therefore, there is a further need to evaluate the use of E or F blends to replace PHO.